FACTORS RELATED TO HIGH QUALITY OF CPR AMONGST PARTICIPANTS IN THE BASIC LIFE SUPPORT TRAINING - Fikriana, Riza (University of Muhammadiyah Malang, 2016)
Cardiac arrest is a condition of downturn which is increasing in numbers. Giving action of qualified Cardiopulmonary Resuscitation (CPR) is one of actions could improve the sustainable life of the patients. The aim of this study was to describe some factors associated with the achievement of high-quality CPR action toward the participants joining basic life support training. The study design uses correlational research with analytic cross-sectional study. The numbers of samples taken are 33 participants in the training of basic life support in the Yogyakarta PUSBANKES 118, and they are taken by purposive sampling technique. The results showed that the high-quality CPR component achieved is average volume ventilation with a median of 590 ml; effective ventilation with a median of 7 times, with a median rate of 107 beats / min and incomplete release of the median is 0. Therefore, based on the analysis of Spearman rho showed a significant relationship between average volume ventilation with an effective amount of ventilation (p-value 0.022), average volume ventilation by age (p-value 0.024), Depthh of chest compressions by body weight (p-value 0.038), chest compression Depthh by height (p-value 0.015), Depthh of chest compressions by sex (p-value 0.003) and incomplete release by body weight (p-value 0.007). High-quality CPR can be influenced by the characteristics of respondents such as age, gender, weight and height.